Interaction Effects of Plasma Vitamins A, E, D, B9, and B12 and Tobacco Exposure in Urothelial Bladder Cancer: A Multifactor Dimensionality Reduction Analysis. (17th November 2019) - Ben Fradj, Mohamed Kacem; Mrad Dali, Kheireddine; Kallel, Amani; Bibi, Mokhtar; Ben Rhouma, Sami; Sanhaji, Haifa; Nouira, Yassine; Feki, Moncef
Abstract: The study aimed to examine circulating vitamins A, E, D, and B12 and folate in patients with urothelial bladder cancer (UBC) and detect potential interaction effects of these micronutrients on UBC risk. A case–control study was conducted on 262 UBC patients and 254 matched controls. Vitamins A and E were assessed by ultra performance liquid chromatography, and vitamins D and B12 and folate were assessed by immunological methods. Binary logistic regression models were used to test associations of plasma vitamins tertiles with UBC risk. A multifactor dimensionality reduction method (MDR) was applied to assess interactive effects of the vitamins and tobacco on UBC risk. Higher levels in vitamins A, E, and D were associated with lower occurrence of UBC. No significant association was observed in plasma folate or vitamin B12 with UBC. There were redundancy interactions of plasma vitamin D with tobacco and with plasma vitamin A on UBC risk. Even though the study could not ascertain causality, the findings suggest that vitamins A, E, and D might be protective against UBC. Vitamins A and D interact antagonistically with each other's and with tobacco to modulate UBC risk. These interactions should be taken in consideration for the prevention of UBC.